5(2x+8)-3=(x+4)

Simple and best practice solution for 5(2x+8)-3=(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(2x+8)-3=(x+4) equation:



5(2x+8)-3=(x+4)
We move all terms to the left:
5(2x+8)-3-((x+4))=0
We multiply parentheses
10x-((x+4))+40-3=0
We calculate terms in parentheses: -((x+4)), so:
(x+4)
We get rid of parentheses
x+4
Back to the equation:
-(x+4)
We add all the numbers together, and all the variables
10x-(x+4)+37=0
We get rid of parentheses
10x-x-4+37=0
We add all the numbers together, and all the variables
9x+33=0
We move all terms containing x to the left, all other terms to the right
9x=-33
x=-33/9
x=-3+2/3

See similar equations:

| 2u=-3+5u | | 8k-3=-59 | | -5x+0.05=-x | | 1/2(1/8x+12)=4 | | 1/2(6x-4)+8-5=12 | | 4x^2+x-9=9x | | x=14=9 | | 24a+4624014=94724072 | | 4(x-1)=12x+12 | | u/3+2=-5 | | 3x-3.75=11.25 | | (5x+5)=(7x-11) | | 3/4x+1=5/6 | | 1+2/3=9+1/2y+1+3/4 | | 4x+16=6x+36 | | 10m=10-5(m-35) | | 5=3v-1 | | 14a+174,142=464,021 | | 11-7d=25 | | (12x+4)=(14x-2) | | =5−3v1 | | 9x+14-7x+21=-4 | | 15y+-4(2y+-3)=-2 | | 18-2x=27 | | 12a+172000=492000 | | 13x-7+110=180 | | 0=144t^2-16t | | 12/3=91/2y+13/4 | | 12x=(-2x) | | 4z/10+5=-16 | | 3x-12=7x-5 | | 6(m-2)=18 |

Equations solver categories